Fractionation and Formulation of Face Serum from Citrus hystrix DC. Fruit Peel Extract as Sunscreen and Skin-Lightening - Widyastuti, Widyastuti; Elmitra, Elmitra; Shinta, Dewi Yudiana; Verawati, Verawati; Afrianti, Ria (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
While the leaves of C. hystrix are commonly traded as cooking spices, their fruit cannot be consumed and is still a waste from the harvest. Scholars strive to take benefit of this fruit, especially after discovering that the C. hystrix fruit peel extract has better sunscreen and skin-lightening activity than their leaf and pulp extract. Therefore, this study aims to examine the sunscreen and skin-lightening activity of this fruit peel extract fraction, which was formulated as a face serum. The fractionation process began by separating ethanol extract and ethyl acetate extract of peel using column chromatography. The separation of extract fractions was based on Retardation factor (Rf) values. Extract fractions and peel extracts were then tested to observe the sunscreen and skin-lightening activity by calculating the Sun Protecting Factor (SPF), Protection grade UVA (PA), DPPH, and tyrosinase inhibition using the spectrophotometric method. Following that, face serum was formulated as gel and emulgel using chitosan and Carbopol-940 as gelling agents. The results showed that the best extract fraction was presented by fraction-6 of fruit peel ethanol extract (FEEP-6) with an SPF value of 26.790 ± 0.028 and fraction-1 of fruit peel ethyl acetate extract (FEAEP-1) with a PA value of 0.609 ± 0.021. Good extract fraction was also shown in fraction-5 of fruit peel ethanol extract (FEEP-5) with an IC50 value against DPPH and tyrosinase of 159.770 ug/mL and 214.156 ug/mL. FEEP-5 was used in the face serum dosage form with a concentration of 0.05%. All face serum dosages met the physical evaluation requirements. The best SPF and antioxidant values of face serum were presented by F4 of 26.505 ± 0.762 and 61.905 ± 0.571%, while the best tyrosinase inhibitor was formulated by F3 of 64.926 ± 0.090%. This study concludes that FEEP-5 and F4 are the best extract fractions and face serum formulas to be used as sunscreen and skin lighteners. In particular, FEEP-5 can be made into a face serum, such as emulgel, sunscreen, and skin lighteners.